Bee Inspired Zonal Vehicle Routing Algorithm in Urban Traffic - Lei Wu; Licai Yang; Haiqing Liu; Yao Zhang (Institute of Advanced Engineering and Science, 2014)
Abstract Dynamic Route Guidance System, which can provide the drivers with the optimal routes, is one of the most efficient solutions to the traffic jam. This paper presents a bee inspired zonal vehicle routing algorithm to provide a reasonable and effective optimal route for the Dynamic Route Guidance System. Firstly, the proposed algorithm divided the whole traffic network into different traffic guidance zone based on Shapley value game. Then, real time traffic data was collected in each traffic guidance zone by inter-vehicle and vehicle-to-infrastructure communications. Ultimately, the proposal simulated the bee foraging phenomenon in the biological system to synchronously compute the optimal routes in each traffic guidance zone. The simulation results show that the algorithm